2018
DOI: 10.1177/0886260518774306
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Coercion Perpetration and Victimization: Gender Similarities and Differences in Adolescence

Abstract: Sexual coercion is a worldwide health problem that endangers the well-being of those involved. In the same line of the most recent and comprehensive studies, this study sought to investigate the extent of sexual coercion, both perpetration and victimization, among male and female adolescents. Moreover, it jointly analyzed the predictive power of different variables that have been considered as useful to design preventive programs. For this purpose, a cross-sectional study, using proportional stratified cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 46 publications
4
30
0
1
Order By: Relevance
“…Regarding links found between sexism and intimate partner violence in adolescent population, it is shown in most of the studies reviewed that both more traditional and more benevolent sexisms predict further justification of domestic violence (Garaigordobil & Aliri, 2013;Shen et al, 2012), greater acceptance of male use of physical violence against women in relationships (Lee et al, 2016;Pozo et al, 2010), and greater violence committed (Fernández-Fuertes et al, 2018;Pazos et al, 2014;Reyes et al, 2016) and suffered (Anacona et al, 2017) in couples. Although the magnitude of the relationship between sexism and gender violence is small (see Anacona et al, 2017;Fernández-Fuertes et al, 2018;Garaigordobil & Aliri, 2013;Lee et al, 2016;Pazos et al, 2014;Pozo et al, 2010;Reyes et al, 2016;Rodríguez-Domínguez et al, 2017;Shen et al, 2012), these data suggest that attitudes emphasizing the difference in roles between genders and the inferiority of women over men, expressed both in a more direct and subtle manner, are associated with more positive attitudes towards violence against women within the couple and the perpetration of violence against the partner among adolescents. However, the results found by Allen et al (2009), in which benevolent sexism would act as a protector of violence being suffered by women and violence committed by men, as well as the null relationship between benevolent sexism and perpetration and victimization of sexual violence or perpetration of cyber-aggression found in other studies (Fernández-Fuertes et al, 2018;Rodríguez-Domínguez et al, 2017), suggest that the different effects that more traditional and more benevolent sexisms can have on variables related to intimate partner violence in adolescent should be further investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding links found between sexism and intimate partner violence in adolescent population, it is shown in most of the studies reviewed that both more traditional and more benevolent sexisms predict further justification of domestic violence (Garaigordobil & Aliri, 2013;Shen et al, 2012), greater acceptance of male use of physical violence against women in relationships (Lee et al, 2016;Pozo et al, 2010), and greater violence committed (Fernández-Fuertes et al, 2018;Pazos et al, 2014;Reyes et al, 2016) and suffered (Anacona et al, 2017) in couples. Although the magnitude of the relationship between sexism and gender violence is small (see Anacona et al, 2017;Fernández-Fuertes et al, 2018;Garaigordobil & Aliri, 2013;Lee et al, 2016;Pazos et al, 2014;Pozo et al, 2010;Reyes et al, 2016;Rodríguez-Domínguez et al, 2017;Shen et al, 2012), these data suggest that attitudes emphasizing the difference in roles between genders and the inferiority of women over men, expressed both in a more direct and subtle manner, are associated with more positive attitudes towards violence against women within the couple and the perpetration of violence against the partner among adolescents. However, the results found by Allen et al (2009), in which benevolent sexism would act as a protector of violence being suffered by women and violence committed by men, as well as the null relationship between benevolent sexism and perpetration and victimization of sexual violence or perpetration of cyber-aggression found in other studies (Fernández-Fuertes et al, 2018;Rodríguez-Domínguez et al, 2017), suggest that the different effects that more traditional and more benevolent sexisms can have on variables related to intimate partner violence in adolescent should be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…benevolent sexism and the perpetration and victimization of sexual violence (Fernández-Fuertes, Carcedo, Orgaz, & Fuertes, 2018) or the perpetration of cyber-aggression (Rodríguez-Domínguez, Durán-Segura, & Martínez-Pecino, 2017). However, other studies show that both more traditional and benevolent sexism are related to a further justification of domestic violence (Garaigordobil & Aliri, 2013;Shen, Chiu, & Gao, 2012), greater acceptance of the use of physical violence against women by men in relationships (Lee, Begun, DePrince, & Chu, 2016;Pozo, Martos, & Alonso, 2010), and greater violence committed (Fernández-Fuertes et al, 2018;Pazos, Oliva, & Hernando, 2014;Reyes, Foshee, Niolon, Reidy, & Hall, 2016) and suffered (Anacona, Cruz, Jiménez, & Guajardo, 2017) in couples. In addition, more traditional sexism predicts greater use of violent strategies of conflict resolution within the couple (Pradas & Perles, 2012) and the perpetration of cyber-aggression towards women by men (Rodríguez-Domínguez et al, 2017).…”
Section: Intimate Partner Violencementioning
confidence: 99%
“…Of all the tactics that can be used, "physical sexual coercion" or "aggression" appears to be the most severe. This direct and invasive type of violence consists of the threat or use of physical force to obtain or attempt to obtain sex (Bagwell-Gray et al, 2015; Fuertes et al, 2018). For its part, verbal sexual coercion is less severe than physical coercion, and includes both positive and negative verbal coercion without force.…”
mentioning
confidence: 99%
“…For its part, verbal sexual coercion is less severe than physical coercion, and includes both positive and negative verbal coercion without force. When "negative verbal sexual coercion" is used, the aggressor gets to have sex by using manipulative and psychological tactics such as verbal pressure, control, manipulation (eliciting feelings of guilt, obligation, or fear of losing the relationship), and extortion (Bagwell-Gray et al, 2015;Fernández-Fuertes et al, 2018;Raghavan et al, 2015;Smith et al, 2018). However, "positive verbal sexual coercion" or "coaxing" includes the use of more subtle tactics that reflect a positive emotional tone, which involves sweettalking and the use of benign and seductive tactics that reflect love and closeness (Camilleri et al, 2009;Livingston et al, 2004).…”
mentioning
confidence: 99%
“…Before ending this section, it is important to mention that positive results of the intervention on gender stereotypes and attitudes toward violence can have a cumulative effect since previous research has shown a clear relationship between sexism and acceptance of gender-based violence (Valor-Segura et al, 2014;Fernández-Fuertes et al, 2018).…”
Section: Gender Stereotypesmentioning
confidence: 99%